CAR-T cells: the Chinese experience. (1st November 2020) - Wang, Linqin; Tan Su Yin, Elaine; Zhao, Houli; Ni, Fang; Hu, Yongxian; Huang, He
ABSTRACT: Introduction: Chimeric antigen receptor T (CAR-T) cells are harnessed to identify and lyse malignant cells specifically, efficiently, and independently of the major histocompatibility complex (MHC). As a result, prognoses of relapsed or refractory (R/R) B cell hematological malignancies as well as limited types of solid tumors, have been ameliorated to a great extent. In China, a rising number of clinical trials that contribute to the development of novel CAR-T therapeutic strategies have been conducted on an extensive scale. Areas covered: We summarize registered clinical trials related to CAR-T therapy conducted in China by evaluating various parameters such as distribution, study phase, CAR structure, target antigen, and disease. The efficacy, toxicity, and, more importantly, the new strategies for optimization of CAR-T therapy of Chinese studies and clinical trials are elaborated in detail. Expert opinion: In terms of the number of CAR-T clinical trials, China is second to the USA, registering approximately 33% of trials worldwide. China's extensive explorations and breakthroughs in the search of novel target antigens, optimization of CAR structure, cocktail CAR-T therapy, combination therapy, and extension of CAR-T cell applications, imply that we are currently on the verge of a revolution in CAR-T therapy.